2020
DOI: 10.1002/adtp.201900177
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Cancer Therapy by Combining Radiation and Chemical Effects Mediated by Nanocarriers

Abstract: Next to surgery, radiotherapy and chemotherapy are the two most commonly applied treatments against cancer. These therapies are often combined, but the therapeutic outcome is still limited. Nanocarriers may be the solution to many of the issues encountered when combining these therapies. In this review, the role of nanocarriers in combined radiotherapy and chemical cancer treatment is discussed, divided into four distinct strategy classes. For each strategy, examples of the literature are given to come eventua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

6
3

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 131 publications
0
18
0
Order By: Relevance
“…Stimuli-responsive polymers are of great interest in nanomedicine since they allow accurate release of drugs at the disease site, while minimizing side effects to healthy tissues. [1][2][3] Such polymers have been used for drug release by encapsulating drugs or directly linking drugs to the polymer side chains. [4][5][6][7] Changes of the polymer physical properties (e.g., the aggregation state) or its chemical structure can lead to drug release, in response to triggers emanating from the body (e.g., pH, temperature, biomarkers, reactive oxygen species (ROS)) or from external sources (e.g., light, heat, magnetic fields, ultrasound).…”
Section: Introductionmentioning
confidence: 99%
“…Stimuli-responsive polymers are of great interest in nanomedicine since they allow accurate release of drugs at the disease site, while minimizing side effects to healthy tissues. [1][2][3] Such polymers have been used for drug release by encapsulating drugs or directly linking drugs to the polymer side chains. [4][5][6][7] Changes of the polymer physical properties (e.g., the aggregation state) or its chemical structure can lead to drug release, in response to triggers emanating from the body (e.g., pH, temperature, biomarkers, reactive oxygen species (ROS)) or from external sources (e.g., light, heat, magnetic fields, ultrasound).…”
Section: Introductionmentioning
confidence: 99%
“…[47] TEM images (Figure 3 respectively. Combined, these analyses demonstrated that both polymers formed micelles with the appropriate size range for nanotherapeutics, [48] and are thus possibly loadable with hydrophobic cargo. [49] Table 2…”
Section: Preparation and Characterization Of P(dman-b-mtpam) Micellesmentioning
confidence: 91%
“…Traditional cancer treatment protocols, such as chemotherapy, surgery, and radiotherapy (RT), have various defects, mainly including invasiveness, limited treatment efficiency, toxic effects, and the risk of tumor recurrence. [1,2] The generation of reactive oxygen species (ROS) to induce oxidative injuries of cancer cells have been extensively applied in various anticancer therapy (e.g., chemotherapy, photodynamic therapy, and RT). [3] As we know, the tumor microenvironment (TME) has characteristics with low pH, hypoxia, elevated concentration of glutathione (GSH), and so on.…”
Section: Introductionmentioning
confidence: 99%